INNOVATIVE PROCESSES IN HEALTHCARE (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The innovative process in healthcare plays a vital role in improving patient outcomes, optimizing treatment efficiency, and reducing healthcare costs. It encompasses the development and implementation of new technologies, procedures, and organizational models aimed at enhancing the quality and accessibility of medical services. Key areas of innovation include telemedicine, artificial intelligence, personalized medicine, and digital health solutions. These advancements not only support clinical decision-making but also foster preventive care and patient engagement. Successful integration of innovations requires a collaborative approach involving medical professionals, researchers, policymakers, and technology developers. As the healthcare sector continues to evolve, the innovative process remains a critical driver of sustainable and effective care delivery.